Analisis Isi dan Bibliometrik Isu Ketenagakerjaan di Indonesia - Nur Saribulan; Saddam Rassanjani; Dahlawi Dahlawi (Journal of Governance and Social Policy, 2023)
The impact of pandemic Covid-19 that produces high unemployment, put labor as the issues most often discussed these days. This study aims to analyze issues relating to employment and its policy in Indonesia by using literature review from a Scopus database for the purpose to describe findings on 1) development publication trend and the highest citation on articles, 2) a map or entanglement articles seen from co-authorship, 3) a map or entanglement articles seen from co-occurrence keywords writer, 4) information related to the issue of articles that have been analyzed. Bibliometric analysis and analysis content used in the following analysis of articles with using Microsoft Excel and Vosviewer software as analyzing and visualizing data tools. The analysis shows that a publication highest seen in 2022 with the total number of 12 articles and article with highest citation named Policies, Political-Economy, and Swidden in Southeast Asia with 208 citations. In terms of mapping articles based on co-authorship formed 57 cluster with Indonesia as a country with the highest writers with total 27 publications. As for the analysis of the map in terms of articles co-occurrence based on keywords writer formed 7 clusters. It is apparent that issues such as the system of remuneration, labor migration, and gender is an issue most frequently discussed in employment associated research.